Gracilis muscle interposition for rectovaginal and anovaginal fistula repair: a systematic literature review. (February 2015) - Hotouras, A.; Ribas, Y.; Zakeri, S.; Murphy, J.; Bhan, C.; Chan, C. L.
Abstract Background Repair of rectovaginal fistula (RVF) is associated with high recurrence. For this reason gracilis muscle interposition is increasingly being used. Aim To evaluate the efficacy of this procedure for RVF repair. Method/Search strategy A search of PubMed and Medline databases was performed in November 2013 using the text terms and MESH headings 'rectovaginal fistula/fistulation', and 'gracilis muscle', spanning 1980–2013. The search strategy was restricted to articles written in English with available abstracts. Sample size, aetiology of RVF, previous repair attempts, follow‐up period, healing rates and complications were recorded and analysed. Results Seventeen studies involving 106 patients were analysed. The cause of RVF included inflammatory bowel disease (n = 37 [34.9%]: Crohn's disease [34], ulcerative colitis [3]), pelvic surgery (37 [34.9%]), obstetric injury (9 [8.5%]), malignancy (7 [6.6%]), trauma (5 [4.7%]), miscellaneous (idiopathic, endometriosis, radiation: 11 [10.4%]). Patients had undergone a median number of two previous unsuccessful repairs. At a median follow‐up of 21 months, healing had occurred in 33–100% (median 100%) with the largest studies reporting rates between 60% and 90%. Thirteen studies did not report any complications, with the remainder reporting only minor morbidity. Conclusion Gracilis interposition appears to have a reasonable success rate for RVF repair with acceptable morbidity. It may be considered as one of the first‐line treatment options for recurrent RVF.